1999
DOI: 10.1006/dbio.1998.9192
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Neural Stem Cells Proliferate in Response to EGF and FGF in the Developing Mouse Telencephalon

Abstract: Multipotent, self-renewing neural stem cells reside in the embryonic mouse telencephalic germinal zone. Using an in vitro neurosphere assay for neural stem cell proliferation, we demonstrate that FGF-responsive neural stem cells are present as early as E8.5 in the anterior neural plate, but EGF-responsive neural stem cells emerge later in development in a temporally and spatially specific manner. By separately blocking EGF and FGF2 signaling, we also show that EGF alone and FGF2 alone can independently elicit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
601
3
8

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 738 publications
(643 citation statements)
references
References 74 publications
31
601
3
8
Order By: Relevance
“…Utilizing in vitro neurosphere assays we showed that EGFR −/− neurospheres did not show the cardinal stem cell traits of self‐renewal (symmetric stem cell division) or full differentiation capability illustrating that EGFR signaling is critical for these processes. These findings support previously published results that EGF and FGF growth factors are important for neural stem cell proliferation 28, 30 but report for the first time the effect complete loss of EGFR has on the neurogenic niche in vivo in postnatal mice. Previous studies have reported the importance of EGFR expression during neural stem cell division with differential EGFR distribution to daughter cells resulting in progenitors with different proliferative, migratory, and differentiation responses to EGFR ligands 7.…”
Section: Discussionsupporting
confidence: 92%
“…Utilizing in vitro neurosphere assays we showed that EGFR −/− neurospheres did not show the cardinal stem cell traits of self‐renewal (symmetric stem cell division) or full differentiation capability illustrating that EGFR signaling is critical for these processes. These findings support previously published results that EGF and FGF growth factors are important for neural stem cell proliferation 28, 30 but report for the first time the effect complete loss of EGFR has on the neurogenic niche in vivo in postnatal mice. Previous studies have reported the importance of EGFR expression during neural stem cell division with differential EGFR distribution to daughter cells resulting in progenitors with different proliferative, migratory, and differentiation responses to EGFR ligands 7.…”
Section: Discussionsupporting
confidence: 92%
“…In experiments employing the selective cannabinoid antagonists AM251 (0.5 µM) and AM630 (0.5 µM), dissociated neurospheres were treated with either antagonists and then diluted, as above, and number of spheres counted after 7 days in culture. In this experiment, the number of new neurospheres was plotted against the initial number of cells plated, and the slope of the lines obtained after the linear regression was used to compare the experimental conditions, from which the behaviour of the NSCs was evaluated (Campos et al, 2004;Tropepe et al, 1999).…”
Section: Neural Stem Cell Proliferation Assaysmentioning
confidence: 99%
“…Embryos were collected from timemated C57/Bl6 mice. The cortex was dissected and mechanically dissociated as described (Tropepe et al, 1999). The cells were spun down and cultured in a 75 cm 2 flask at 10 cells/ml in neurosphere medium composed of a 1:1 mixture of DMEM and F12 nutrient (Invitrogen) containing 0.6% glucose, 2 mM glutamine, 13 mM sodium bicarbonate, 5 mM N-2-hydroxyethylpiperazine-N 0 -2-ethanesulfonic acid (HEPES) buffer, 5 IU/ml penicillin and 5 mg/ml streptomycin, and the B27, N-2 and G5 supplements (10 ml/ml each, Invitrogen).…”
Section: Cell Culture Preparationsmentioning
confidence: 99%